Financial Stress, Downturns, and Recoveries - Lall, Subir (IMF Working Papers; Working Paper ;, 2009)
This paper examines why some financial stress episodes lead to economic downturns. The paper identifies episodes of financial turmoil using a financial stress index (FSI), and proposes an analytical framework to assess the impact of financial stress-in particular banking distress-on the real economy. It concludes that financial turmoil characterized by banking distress is more likely to be associated with severe and protracted downturns than stress mainly in securities or foreign exchange markets. Economies with more arms-length financial systems appear to be particularly vulnerable to sharp contractions, due to the greater procyclicality of leverage in their banking systems.